Sustainable Storytelling in Digital Climate Campaigns: A Comparative Analysis of Visual Communication Strategies - Gyeol, Jang Han; Ho, Song Ji; Woo, Song Jin (International Journal of Graphic Design, 2025)
Climate change requires urgent and strategic communication efforts to inspire public awareness and behavioral change. This study investigates the comparative effectiveness of three visual storytelling strategies—data visualization, interactive infographics, and narrative illustration—on digital platforms in shaping public comprehension, emotional response, and behavioral intention regarding climate change. A pretest-posttest control group experiment was conducted involving 120 participants aged 18–35, randomly divided into four groups. Each experimental group was exposed to one of the three visual strategies, while the control group received text-based narratives. Measurement instruments included a 10-item comprehension test, the Positive and Negative Affect Schedule (PANAS), and a behavioral intention scale. Statistical analysis using one-way ANOVA and Tukey’s post-hoc test revealed significant differences (p < 0.01) among the groups. Interactive infographics consistently produced the highest gains in comprehension (+3.1), positive emotional response (+2.7), and behavioral intention (+3.4), followed by narrative illustrations. Data visualizations were most effective for cognitive understanding but less emotionally engaging. The findings support the Elaboration Likelihood Model by highlighting how different visual modalities engage both rational and affective pathways. This study contributes theoretically to affective computing and practically to climate communication design by recommending visual strategies tailored to maximize public engagement and sustainability impact. Future studies are encouraged to explore longitudinal effects and cultural contexts in environmental storytelling.